Match or Mismatch? Attempting a Feminist Pedagogy for a Course on Biblical Criticisms - McKinlay, Judith E. (Teaching theology and religion, 2000)
This paper reports on a project undertaken as part of a wider group exploration of feminist pedagogy. It reflects on the issues this raised in teaching a course on contemporary biblical criticisms, an area of biblical studies where questions of power and ideology are frequently asked of texts. The project therefore asked the question whether there was a match or mismatch between the teaching process and the content of the course. Of particular concern was the understanding of the role of the teacher, the lecturer's ‘what am I doing in this class?’ question. The move to open up the student space led to the matter of boundaries. Who decides upon and regulates the limits of what can be discussed? What allows trust in a class and how does one deal with feelings and emotions? This paper engages the class members on all these issues, drawing on their comments gained from the questionnaire that was part of the project design.